2013
DOI: 10.1116/1.4840255
|View full text |Cite
|
Sign up to set email alerts
|

Microcathodoluminescence spectra evolution for planar and nanopillar multiquantum-well GaN-based structures as a function of electron irradiation dose

Abstract: Articles you may be interested inNano-scale luminescence characterization of individual InGaN/GaN quantum wells stacked in a microcavity using scanning transmission electron microscope cathodoluminescence Appl. Phys. Lett. 105, 032101 (2014); 10.1063/1.4890670 High resolution cathodoluminescence hyperspectral imaging of surface features in InGaN/GaN multiple quantum well structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…These facts also allow to exclude the surface‐related mechanisms and other explanation of effects observed should be found. The comparison of LEEBI effect on the planar structure and nanopillars formed on this structure by dry etching shows that the shift values of MQW related emission line after LEEBI and after nanopillar formation procedure are practically the same . As shown in Refs.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…These facts also allow to exclude the surface‐related mechanisms and other explanation of effects observed should be found. The comparison of LEEBI effect on the planar structure and nanopillars formed on this structure by dry etching shows that the shift values of MQW related emission line after LEEBI and after nanopillar formation procedure are practically the same . As shown in Refs.…”
Section: Introductionmentioning
confidence: 55%
“…). The effects of low energy electron beam irradiation (LEEBI) on optical properties of InGaN/GaN structures with multiple quantum wells (MQW) have been studied in numerous papers because this point is important not only for the adequate characterization of such structures by the SEM methods but also for evaluating the light emitting diodes (LEDs) stability under prolonged high forward current, photon or electron beam injection. It was observed that LEEBI leads to an essential increase in the cathodoluminescence (CL) intensity (by more than two orders of magnitude in some structures) and to a blue shift of MQW‐related emission band.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal etching is a process that utilizes high temperatures to reveal specific grooves at interface boundaries between materials. Another method by Yakimov et al tested the inclusion of low energy electron beam irradiation (LEEBI) on planar and nanopillar LED structures in order to enhance emissions from the device [5]. Their results demonstrated a blue shift of emission (from 2.92 eV to 2.98 ev) along with an increase in intensity from InGaN/GaN multiple quantum wells (MQWs) due to excitation of the lower n-GaN layer through the fabricated holes as well as decrease of strain and piezoelectric field in the quantum wells.…”
Section: Processing Methods To Enhance Performancementioning
confidence: 99%
“…This underlines the difficulties in suppressing the leakage current in nanopillar p‐n junctions that are related to the more prominent influence of surface bending causing additional leakage. It has been also noted that, because of the proximity of the quantum wells to the nanopillars sidewalls certain structural changes can occur in quantum wells under the probing beam of the scanning microscope (and very likely, under high driving current flow during LED operation) and can result in measurable changes in energy and intensity of the MQW peak. It can be pointed out that the surface leakage and MQW intensity variations problems are mostly a consequence of the enhanced impact of the sidewalls surface and should also present a problem for the bottom‐up NW LED structures prepared by growth .…”
Section: Mitigating the Dry Etching Defects Damagementioning
confidence: 99%
“…In refs. , we tried to organize contacting by transferring on top of the nanopillar LED structure multilayer graphene films with light annealing at very moderate temperatures. These LEDs work, the advantage is the process simplicity (given, of course, that good quality graphene films are already available), but the series resistance turns out to be on the high side.…”
Section: Examples Of Beneficial Use Of the Top‐down Approachmentioning
confidence: 99%